Association between self-reported eating speed and metabolic syndrome in a Beijing adult population: a cross-sectional study - Lixin Tao; Kun Yang; Fangfang Huang; Xiangtong Liu; Xia Li; Yanxia Luo; Lijuan Wu; Xiuhua Guo (BMC, 2018)
Abstract Background Research on the relationship between metabolic syndrome (MetS), its components and eating speed is limited in China. The present study aimed to clarify the association between MetS, its components and eating speed in a Beijing adult population. Methods This cross-sectional study included 7972 adults who were 18-65 years old and who received health check-ups at the Beijing Physical Examination Center in 2016. Logistic regression was conducted to explore the associations between MetS, its components and eating speed. Results The prevalence of MetS in this population was 24.65% (36.02% for males and 10.18% for females). Eating speed was significantly associated with a high risk for MetS, elevated blood pressure, and central obesity for both genders. Eating speed was associated with a high risk for elevated triglycerides and with a reduction in high-density lipoprotein in males, and eating speed was associated with a high risk for elevated fasting plasma glucose in females. Compared with slow eating speed, the multivariate-adjusted odds ratios of medium eating speed and fast eating speed for MetS were 1.65 (95% confidence interval 1.32-2.07) and 2.27 (95% confidence interval 1.80-2.86) for all subjects, 1.58 (95% confidence interval 1.21-2.07) and 2.21 (95% confidence interval 1.69-2.91) for males, and 1.75 (95% confidence interval 1.15-2.68) and 2.27 (95% confidence interval 1.46-3.53) for females, respectively. Conclusions Eating speed is positively associated with MetS and its components. Future recommendations aiming to prevent MetS and its components may focus on eating speed.